Challenges for unaccompanied asylum-seeking minors in Swedish compulsory institutional care - Stjerna Doohan, Isabelle; Ghazinour, Mehdi; Eriksson, Malin; Padyab, Mojgan; Sundqvist, Johanna (Frontiers in Human Dynamics, 2024)
This qualitative thematic study aimed to examine the placement of unaccompanied asylum-seeking minors in compulsory institutional care in Sweden, to expand knowledge regarding their care and treatment. The dataset comprised official documents and anonymized journal documents from personnel detailing the experiences of twenty-five unaccompanied asylum-seeking minors in compulsory institutional care organized by the Swedish National Board of Institutional Care in 2015. The study identified three main themes: traumatic life events and mental health, alignment between needs, goals, and treatment, and language difficulties. The findings revealed a high prevalence of severe traumatic experiences among the asylum-seeking minors, with half having endured significant psychological and physical trauma. Mental health issues were inconsistently addressed, and prior traumas were often overlooked in care planning. The majority exhibited various mental health problems, underscoring the need for tailored interventions. The study highlights challenges in aligning unaccompanied asylum-seeking minors' individual needs, treatment goals, and provided care. Language barriers emerged as a critical concern, impeding effective communication and treatment. Approximately 80% of the asylum-seeking minors experienced difficulties in understanding and expressing themselves in Swedish. The limited use of professional interpreters further exacerbated this issue. The study underscores the need for targeted interventions to better support unaccompanied asylum-seeking minors within compulsory institutional settings.